17.2k views
0 votes
Solve the system by substitution.
y= -6x-7
y= -7x

User PREEB
by
4.2k points

2 Answers

8 votes

Answer:

X = 7 Y = -49

Explanation:

Y= -6 X -7---------(1)

Y= -7 X ------------(2)

using substitution method, substitute equation two into equation one

-7 X = -6X -7

-7 X+6X = -7

- X = -7

cancelling the - sign on bothsides

X = 7

put X = 7 into equation (2)

Y = -7(7)

Y = -49

therefore, X = 7 Y= -49

User Sandeep Patel
by
4.2k points
5 votes

Answer:

x = 7

y = -49

Explanation:

Solving system of equation by substitution method.

y = -6x - 7 ---------------(I)

y = -7x -------------------(II)

Substitute y = -7x in equation (I)

-7x = -6x - 7

-7x + 6x = -7

-x = -7

Multiply both sides by (-1)


\sf \boxed{\bf x = 7}

Substitute x =7 in equation (II)

y = -7*7


\sf \boxed{\bf y = -49}

User Mike Brant
by
4.9k points